Экономическое и юридическое понимание права собственности - Щербакова, Екатерина (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an analysis of the property right law system in the civil law of the Russian Federation. Presenting the construction of the right to property the author take into consideration both the economical and legal perspective.